2022
DOI: 10.3389/fdgth.2022.961128
|View full text |Cite
|
Sign up to set email alerts
|

Barriers, interventions, and recommendations: Improving the genetic testing landscape

Abstract: Individual, provider, clinic, and societal level barriers have been shown to undermine the potential impact of genetic testing. The current approach in the primary care setting places an exorbitant burden on both providers and patients. Current literature provides insight into how to address barriers across multiple levels (patient, provider, clinic, system) and at multiple stages in the testing process (identification, referral, counseling, and testing) but interventions have had limited success. After outlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…20 In addition to covering the cost of the actual test, it is unclear whether coverage will be provided at the individual level for subsequent genetic counseling services and follow-up visits, disinclining patients toward germline testing. 21 Additionally, patients become concerned about genetic discrimination when it comes to other insurance policies such as to long-term care, disability, and/or life insurance. 22 These pose formidable obstacles and we strongly advocate for insurance plans to provide coverage for germline testing and clinical genetics assessments in patients who have compelling indications to undergo such testing and seamless protection against discrimination in accordance to the Genetic Information Nondiscrimination Act.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…20 In addition to covering the cost of the actual test, it is unclear whether coverage will be provided at the individual level for subsequent genetic counseling services and follow-up visits, disinclining patients toward germline testing. 21 Additionally, patients become concerned about genetic discrimination when it comes to other insurance policies such as to long-term care, disability, and/or life insurance. 22 These pose formidable obstacles and we strongly advocate for insurance plans to provide coverage for germline testing and clinical genetics assessments in patients who have compelling indications to undergo such testing and seamless protection against discrimination in accordance to the Genetic Information Nondiscrimination Act.…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, these criteria are not necessarily up to date with guideline recommendations and exclude coverage for many patients whose medical histories indicate germline testing 20 . In addition to covering the cost of the actual test, it is unclear whether coverage will be provided at the individual level for subsequent genetic counseling services and follow‐up visits, disinclining patients toward germline testing 21 . Additionally, patients become concerned about genetic discrimination when it comes to other insurance policies such as to long‐term care, disability, and/or life insurance 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Feasibility, appropriateness and penetration are outcomes most frequently examined, while cost, fidelity and sustainability are often overlooked. Cost is often a factor that is cited by studies as a barrier to cascade testing 18 , 49 . Three out of 27 studies evaluated cost and showed that offering free cascade testing can remove a significant barrier, but this requires either further investment in a budget-constrained healthcare system or third-party payers.…”
Section: Discussionmentioning
confidence: 99%
“…Comprising eight items on a scale of 1 to 3, responses ranged from agreement to disagreement. The items were rephrased from previous studies [11][12][13] with some modifications. The total attitude score ranged from 1 to 24, and respondents scoring 60% or above were considered to have a positive attitude toward genetic testing.…”
Section: Data Collection Toolsmentioning
confidence: 99%